Impacto de la corrupción política y la migración neta sobre los homicidios intencionales en Ecuador durante 1990 - 2023, considerando roturas estructurales - Carrión Armijos, Evelyn María (2025)
Ecuador has experienced an exponential growth in intentional homicides in recent years, which has led the country to be among the most violent countries in Latin America. The increase in violent deaths is associated with economic, social, and political factors. The main objective of this research is to examine the relationship between political corruption, net migration, and intentional homicides in Ecuador during the period 1990 - 2023, considering structural breaks. Using time series techniques, we found that the variables present a long-term equilibrium relationship. It was determined that political corruption is indirectly influenced by weakening institutions and promoting inequality. For its part, net migration has a dual impact: immigration tends to reduce homicides by boosting the economy, while emigration increases levels of violence due to the loss of human capital and family disintegration. Likewise, it was shown that cultural globalization is associated with an increase in violence due to its link with illicit trafficking and exposure to values that promote violent behavior in unequal contexts. The results emphasize the need to strengthen institutions, combat political corruption, and manage migration flows comprehensively, along with implementing policies to reduce inequality and promote economic development. These actions are key to reducing violence rates, improving security in Ecuador, and achieving Sustainable Development Goal 16.